Teacher Labor Markets in Developing Countries - Lee Crawfurd; Todd Pugatch (Institute of Labor Economics (IZA), 2020)
The types of workers recruited into teaching and their allocation across classrooms can greatly influence a country's stock of human capital. This paper considers how markets and non-market institutions determine the quantity, wages, skills, and spatial distribution of teachers in developing countries. Schools are a major source of employment in developing countries, particularly for women and professionals. Teacher compensation is also a large share of public budgets. Teacher labor markets in developing countries are likely to grow further as teacher quality becomes a greater focus of education policy, including under the United Nations Sustainable Development Goals. Theoretical approaches to teacher labor markets have emphasized the role of non-market institutions, such as government and unions, and other frictions in teacher employment and wages. The evidence supports the existence and importance of such frictions in how teacher labor markets function. In many countries, large gaps in pay and quality exist between teachers and other professionals; teachers in public and private schools; teachers on permanent and temporary contracts; and teachers in urban and rural areas. Teacher supply increases with wages, though teacher quality does not necessarily increase. However, most evidence comes from studies of short-term effects among existing teachers. Evidence on effects in the long-term, on the supply of new teachers, or on changes in non-pecuniary compensation is scarcer.
Keywords: J44; J45; J31; J21; J23; I28; 330; teacher labor markets; developing countries; public sector labor markets; education; public service delivery